Purwarupa Sistem Informasi Desa Matano - Smartano dalam Rangka Penguatan Pemasaran Hasil Pertanian Lada dan Promosi Wisata Desa Matano - Nirsal, Nirsal; Nurfalaq, Aryadi; Naim, Muhammad; Idkhan, A. Muhammad; Kaswar, Andi Baso; Muhtar, Hafidz; Sari, Sartika; R, Ranir Aftar; Darme, Agustinus Suria; Rapa, Wiwi; Bantun, Suharsono; Sari, Jayanti Yusmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Matano Village has great potential in the agricultural sector, especially pepper production, as well as tourism potential that has been recognized nationally. This article discusses the development of a prototype of the Matano Village Information System, called Smartano, as a digital solution to integrate pepper agricultural product marketing and village tourism promotion. This system is designed to provide support for the local community in increasing the competitiveness of pepper products in the market and optimizing the tourism potential of Matano Village through an information technology-based approach.